PERLINDUNGAN HUKUM TERHADAP PIHAK TERTANGGUNG DALAM ASURANSI DEMAM BERDARAH PADA PT. ASURANSI CENTRAL ASIA - Charisma Putra, Darmadi; Markeling, I Ketut; Dedy Priyanto, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014)
Insurance is an agreement in which the parties committed themselves to the insured and receive a premium to provide reimbursement to the insured for losses arising from an uncertain events as well as written in the deed called the policy, therefore the author will explain how the legal protection given to the insured and remedies that can be taken to get insured in an insurance claim for the loss of dengue in PT. Asuransi Central Asia or the ACA. Study is a juridical empirical legal research. Legal protection given to the insured in the insurance dengue in the ACA that do not have a policy does not expressly provided in the Act , the legal protection given by the consensual nature of the insurance agreement and remedies that can be taken to get the insurance claim insured dengue is to file a lawsuit before a court , arbitration or mediation body , the insured must bear all costs in its efforts to obtain compensation , which according to article 283 Kitab Undang-Undang Hukum Dagang or KUHD insurer must bear all the costs of the insured.
Keywords: Insurance, Protection, Remedies